Study of Some Chemical (Peroxide Number) and Bacterial Changes Using Sheep Fat on Meat Broiler (Journal of Hama University, 2022)
This study was conducted to find out the effect of adding sheep fat to broiler meat on bacterial count and peroxide number to determine the best percentage of fat added to broiler meat in order to preserve it without spoiling for as long as possible. To achieve this, the experiment was conducted on five groups of broiler meat with different percentages of sheep fat added according to the following:B (Control) broiler meat only, nothing was added to it, B1 (broiler meat + 15% fat), B2 (broiler meat + 20% fat), B3 (broiler meat + 25% fat), B4 (broiler meat + 30% fat). Then the peroxide number was measured and a general bacterial count was performed on days (1-2-3-7) after keeping the study groups at a temperature of +4°C, and on days (1-2) after keeping the study groups at a temperature of +25°C. Results showed that There were no significant differences at (P